Towards the Implementation of Patterns of Environmental Sustainability in Production and Consumption: Sustainable Public Procurement - Soto Palacios, Miguel Ángel (2014)
Public spending of many states makes a significant contribution to the Gross Domestic Product of countries, which are the main consumers of the national economies. For this reason, the purchasing power is an opportunity to influence the market by promoting production and consumption of sustainable and friendly goods to the environment.In this sense, this article discusses the system of Sustainable Public Procurements as a way to promote Sustainable Consumption and Production patterns and, thus, reach sustainable development for a green economy.